Aortic Root Replacement in a Patient with Bicuspid Pulmonary Valve Late after Arterial Switch Operation - Bobylev, Dmitry; Breymann, Thomas; Boethig, Dietmar; Ono, Masamichi (The Thoracic and Cardiovascular Surgeon, 2013)
Mild to moderate neoaortic root dilatation late after arterial switch operation (ASO) is a well-documented morbidity, but rarely needs surgical replacement. Here, we report on a 22-year-old man, who developed marked dilatation of neoaortic root and needed an aortic root replacement with mechanical conduit. His aortic valve was bicuspid. Only three cases have been reported for surgical replacement of aortic root after ASO, and two of them had bicuspid neoaortic valves. We suspect that a bicuspid neoaortic valve may be a risk factor for marked dilatation of the aortic root late after ASO.
Keywords: transposition of the great arteries; arterial switch operation; bicuspid neoaortic valve